2022
DOI: 10.5032/jae.2022.04001
|View full text |Cite
|
Sign up to set email alerts
|

Describing College Success Indicators for First-Generation College Students in Colleges of Agriculture

Abstract: Earning a bachelor’s degree has been documented as a potential social equalizer in American society. Yet, it has also been documented that first-generation college students (FGCS) have incongruently accessed and earned college degrees. This phenomenon has potentially perpetuated life-long differences in social outcomes in American society. As research continues to explain the experiences of FGCS, little has been done to explore differences for FGCS by college major or affiliation. However, a small but growing … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 32 publications
0
2
0
Order By: Relevance
“…First, respondents generally perceived they had a strong sense of belonging to both AFLS and the University of Arkansas. Furthermore, the students in this study had a higher perceived sense of belonging than the participants in Giorgi et al's (2022) study. Students' perceptions of peer support, faculty support, classroom comfort, and empathetic/understanding faculty were lower than their perceived sense of belonging.…”
Section: Conclusion/discussion/implications/ Recommendationsmentioning
confidence: 56%
See 1 more Smart Citation
“…First, respondents generally perceived they had a strong sense of belonging to both AFLS and the University of Arkansas. Furthermore, the students in this study had a higher perceived sense of belonging than the participants in Giorgi et al's (2022) study. Students' perceptions of peer support, faculty support, classroom comfort, and empathetic/understanding faculty were lower than their perceived sense of belonging.…”
Section: Conclusion/discussion/implications/ Recommendationsmentioning
confidence: 56%
“…Conversely, in the absence of sense of belonging, students may become disengaged with education-related activities, feel isolated, and be at increased risk of leaving the institution (Strayhorn, 2018). Sense of belonging research among college of agriculture students is limited, however, Giorgi et al (2022) found that agriculture students possessed a moderate sense of belonging to their college of agriculture with first-generation college students reporting the highest scores. Because sense of belonging has been shown to be an important factor related to student retention and a dearth of literature exists pertaining to students in colleges of agriculture, this study is warranted.…”
Section: Conceptual Frameworkmentioning
confidence: 99%